Improving enzymatic polyurethane hydrolysis by tuning enzyme sorption. (October 2016) - Gamerith, Caroline; Herrero Acero, Enrique; Pellis, Alessandro; Ortner, Andreas; Vielnascher, Robert; Luschnig, Daniel; Zartl, Barbara; Haernvall, Karolina; Zitzenbacher, Sabine; Strohmeier, Gernot; Hoff, Oskar; Steinkellner, Georg; et al.
Abstract: In this study we investigated the ability of amidases to hydrolyse polyurethane polyester co-polymers. In order to improve enzyme adsorption, a polyamidase from Nocardia farcinica (PA) was fused to a polymer binding module from a polyhydroxyalkanoate depolymerase from Alcaligenes faecalis (PA_PBM). The activity of these enzymes and of various commercially available amidases on a synthesized soluble model substrate was compared. The recombinant native PA showed the highest activity of 10.5 U/mg followed by PA_PBM with an activity of 1.13 U/mg. Both enzymes were able to cleave the urethane bond in polyurethane-polyesters with different degree of crystallinity as shown by FTIR. According to LC-TOF analysis the monomer 4, 4′-diaminodiphenylmethane (MDA) and the oligomers 4-hydroxybutyl (3-(3-aminobenzyl)phenyl)carbamate [B], bis(4-hydroxybutyl) (methylenebis(3, 1-phenylene))dicarbamate [C] and 4-(((3-(3-(((4-hydroxybutoxy)carbonyl)amino)benzyl)phenyl)carbamoyl)oxy)butyl (4-hydroxybutyl) adipate [D] were released. The polymer with a higher content of the rigid segment, MDA, was hydrolysed to a lower extent. Interestingly, despite the lower activity on the soluble model substrate, the PA_PBM fusion enzyme was up to 4 times more active on the polymer when compared with the native enzyme, confirming the relevance of enzyme adsorption for efficient hydrolysis. Graphical abstract: Scheme of enzymatic PU hydrolysis by PA or PA_PBM leading to the release of 4, 4′-diaminodiphenylmethane.